Detection of mycoplasma species in turkeys by culture and polymerase chain reaction - Ongor, H.; Kalin, R.; Karahan, M.; Cetinkaya, B.; Akan, M. (Office Int Epizooties, 2009)
The purpose of the present study was to investigate the presence of pathogenic mycoplasma species in the turkey population of Turkey. Tracheal samples randomly collected from a total of 624 apparently healthy meat-type turkeys at a commercial abattoir located in the north of the country were examined by culture and genus- and species-specific polymerase chain reaction (PCR) assays for mycoplasma. In the direct plating onto solid specific media, mycoplasma growth was observed from 1.4% (9/624) of the samples, which were confirmed to belong to the Mycoplasma genus by genus-specific PCR. Mycoplasma iowae (MI) and M. meleagridis (MM) were identified by the species-specific PCR from eight and one of the samples, respectively. However, genus-specific PCR amplification was obtained from 2.6% (16/624) of the samples which produced turbidity in the liquid media. Interestingly, these positive samples were different from those obtained from solid agar and mycoplasma growth was not observed when the broth samples were inoculated onto solid media. In the species-specific PCR analysis of the broth samples, MI, MM and M. gallisepticum were identified from twelve, two and two samples, respectively. The inconsistency between the results obtained from liquid and solid media raises questions about the efficiency of isolation procedures for mycoplasma and this warrants further investigation.
Keywords: Mycoplasma; Polymerase chain reaction; Trachea; Turkey; Turkeys